(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Growth is affected by internal and external factors. External factor consist of postnatal factor, one of them is nutrition including breastmilk. Nutritional elements become the most dominan influence in children’s growth, especially in early life up to 12 month. The coverage of Exclusive Breastfeeding (EBF) in Jetis Public Health Center are 77,11%, but the prevalence of fat toddler and skinny toddler also high (9,82% and 8,02%). Objective: Knowing the association of EBF and baby’s growth in working area of Puskesmas Jetis. Method: This study was an observational with crossectional design. This study conducted in May 2019. Sample were 59 babies aged 6-9 months old. Sampling technique used was purposive sampling. Data analysis using chi square with alpa 0,05. Result: Among 44 babies who got exclusive breastfeed, 97,7% of them experience normal growth. While among 15 babies who didn’t get exclusive breastfeed, 66,7% of them experience normal growth. From chi square test obtained significant result between EBF and baby’s growth with p value=0,003, RP=1,4 with CI 95% (1,022-2,103). Conclution: EBF increase the normal growth of babies aged 6-9 months old in Jetis Public Health Center area by 1,4 times. Keywords: relationships, exclusive breastfeeding, growth